2018
DOI: 10.1002/ejoc.201800669
|View full text |Cite
|
Sign up to set email alerts
|

Ni(ClO4)2‐Catalyzed Friedel–Crafts Reaction of Coumarin‐Fused Donor–Acceptor Cyclopropanes with Indoles: Stereoselective Synthesis of trans‐3,4‐Disubstituted‐3,4‐dihydrocoumarins

Abstract: A stereoselective synthesis of trans‐4‐(3‐indolylmethyl)‐3,4‐dihydrocoumarins has been developed. The method proceeds through a catalytic Friedel–Crafts reaction of coumarin‐fused donor–acceptor cyclopropanes with indoles. The use of Ni(ClO4)2 as a Lewis acid catalyst leads to the formation of a variety of 4‐(3‐indolylmethyl)‐3,4‐dihydrocoumarins in good yields with high diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Fur-thermore, the reaction between 2-methylindole and coumarin fused cyclopropane 1a proceeded smoothly to furnish the desired 3,4-dihydrocoumarin 3j in 98 % yield with excellent diastereoselectivity. The relative stereochemistry of 3a was confirmed by X-ray crystallographic analysis, [15] in which the indolylmethylene group was found to be trans to the ester group (Figure 2). The configurations of the other products were assigned by analogy.…”
Section: Resultsmentioning
confidence: 84%
“…Fur-thermore, the reaction between 2-methylindole and coumarin fused cyclopropane 1a proceeded smoothly to furnish the desired 3,4-dihydrocoumarin 3j in 98 % yield with excellent diastereoselectivity. The relative stereochemistry of 3a was confirmed by X-ray crystallographic analysis, [15] in which the indolylmethylene group was found to be trans to the ester group (Figure 2). The configurations of the other products were assigned by analogy.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, this cyclopropacoumarin remains intact under heating with both tin(II) triflate in dichloromethane and trimethylsilyl triflate in chlorobenzene for several hours. The absence of benzoxepane derivative in the reaction mixtures together with the aforementioned literature data on the nucleophilic attack of cyclopa[ c ]coumarins at the CH 2 atom [34] demonstrate the decelerating effect of annulation on the reactivity of the C-C bond between atoms connected to donor and acceptor substituents. The effect of the annulated ring nature on the reactivity of donor-acceptor cyclopropanes deserve, evidently, a careful study.…”
Section: Resultsmentioning
confidence: 86%
“…The obtained cyclopropa[ c ]coumarins 2 are potent substrates for the synthesis of diverse coumarin derivatives (Scheme 5). Thus, it was recently shown that such cyclopropacoumarins undergo Ni(ClO 4 ) 2 -catalyzed nucleophilic ring opening under treatment with indole affording 4-(indolylmethyl)chroman-2-one-3-carboxylates [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations